2022
DOI: 10.34067/kid.0007002021
|View full text |Cite
|
Sign up to set email alerts
|

Global Dialysis Perspective: Uganda

Abstract: This is an Early Access article. Please select the PDF button, above, to view it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Proteinuria is a biomarker for kidney injury [28]; thus further research into context-speci c risk factors for kidney disease is needed to understand the cause of kidney injury in older PLWH. Kidney disease is progressive; thus these ndings of the excess prevalence of kidney function impairment and proteinuria may have implications for the health and survival of old PLWH in a country where there is limited access to life-saving therapies such as dialysis and renal transplants for kidney failure [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteinuria is a biomarker for kidney injury [28]; thus further research into context-speci c risk factors for kidney disease is needed to understand the cause of kidney injury in older PLWH. Kidney disease is progressive; thus these ndings of the excess prevalence of kidney function impairment and proteinuria may have implications for the health and survival of old PLWH in a country where there is limited access to life-saving therapies such as dialysis and renal transplants for kidney failure [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney failure is associated with increased morbidity, poor quality of life, and increased risk of death among PLWH [11][12][13][14]. In low-income countries (LICs) such as Uganda, there is limited access to life-saving dialysis and kidney transplants to manage end-stage kidney disease(ESKD)/kidney failure and even when available, the costs exceed the average income for most patients [15,16]. Studies in the general population have documented the association of HIV with kidney disease in both low-and high-resource settings [17][18][19][20], but there is a paucity of data documenting the excess prevalence of kidney function impairment in older PLWH in Uganda and sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In East Africa, most of the cases of hyperkalaemia are reported to be caused by: Acute kidney injury (AKI), Chronic kidney disease, Serum electrolytes and risk factors in Diabetic patients, Drug-drug interactions, Renal failure, Drug therapy problems, Tumour lysis syndrome and Post-Cardiac Arrest as shown in the table of results. In Uganda, majority of chronic kidney diseases are presented at late stages when they have already developed advanced complications like electrolyte imbalances such as hyperkalaemia [20] and it has been reported that people with normally functioning kidneys have equal chances of developing hyperkalaemia [21].…”
Section: Discussionmentioning
confidence: 99%
“…Sustainability is not a priority for patients when most cannot afford medications, transplantation, or dialysis, such as in Uganda, where 90% of patients in need of kidney replacement therapy cannot afford it. 26 In addition, access to care is inequitable as most dialysis and transplant programs are located in urban centers, 14 , 20 and many patients incur substantial out-of-pocket expenses ( Table 1 ).…”
Section: Barriers To Implementing Environmentally Sustainable Kidney ...mentioning
confidence: 99%